The evolving relationship between adiponectin and insulin sensitivity in hepatitis C patients during viral clearance. Issue 7 (3rd October 2017) - Chang, Ming-Ling; Kuo, Chia-Jung; Pao, Li-Heng; Hsu, Chen-Ming; Chiu, Cheng-Tang
ABSTRACT: Background : The evolution of the relationship between adiponectin and insulin sensitivity in hepatitis C virus (HCV) patients during viral clearance is unclear and warrants investigation.Methods : A prospective study including 747 consecutive chronic hepatitis C (CHC) patients, of whom 546 had completed a course of anti-HCV therapy and underwent pre-, peri- and post-therapy surveys for anthropomorphic, viral, metabolic and hepatic profiles and adiponectin levels, was conducted in a tertiary care center.Results : Multivariate analyses indicated associations of sex, triglyceride levels and hepatic steatosis with adiponectin levels and of triglyceride levels and interferon λ3 (IFNL3) genotype with homeostasis model assessment-estimated insulin resistance (HOMA-IR) levels before anti-HCV therapy. In patients with a sustained virological response (SVR; n = 455), at 24 weeks post-therapy, sex, BMI, aspartate aminotransferase to platelet ratio index (APRI), HOMA-IR and steatosis were associated with adiponectin levels, and IFNL3 genotype was associated with HOMA-IR levels. GEE analysis demonstrated that SVR affected longitudinal trends in adiponectin levels. Compared with pre-therapy levels, adiponectin and APRI levels decreased 24 weeks post-therapy in SVR patients, regardless of baseline insulin resistance (IR). However, HOMA-IR levels decreased in SVR patients with baseline IR but increased in those without baseline IR. Compared with controls, immunohistochemical studies showed that pre-therapy CHC patients had higher hepatic adiponectin expression associated with hepatic fibrosis.Conclusions : During HCV infection, adiponectin may affect insulin sensitivity through triglycerides. After viral clearance, adiponectin levels were directly associated with insulin sensitivity and decreased upon improved hepatic fibrosis; with a link to the IFNL3 genotype, insulin sensitivity improved only in patients with baseline IR.